AIRPORTS AS AN ATTRACTION: A CASE STUDY OF CHANGI AND INCHEON INTERNATIONAL AIRPORTS - Byeong Du Kim (Tạp chí Khoa học Đại học Đà Lạt, 2024)
Airports in Singapore and the Republic of Korea have higher passenger traffic than those in neighboring countries. This may be because Changi International Airport in Singapore and Incheon International Airport in Korea are not only functional but also attractions. Such airports are beneficial during national crises, such as pandemics and economic downturns, because they serve as tourist attractions. This study examines the services offered by these two airports to identify factors that could help Vietnamese airports enhance their services. The results indicate that Vietnamese airports should provide cultural amenities consistently across all terminals. However, as Changi and Incheon International Airports are larger than Vietnam’s airports, future studies should focus on smaller airports, such as Tan Son Nhat Airport, to investigate methods to attract tourists.